Manufacture of titanium dioxide scaffolds for medical applications (2018)
The skeletal system is vulnerable to injuries and bone loss over the years, making the use of autologous or allogeneic implants necessary. However, these implants have complications, such as the limited amount of bone to be extracted and the cell death at the extraction site; hence, biomaterials have been developed as platforms for cell growth (scaffolds). Biomaterials and bones have similar properties that facilitate the integration between the material and the bone tissue, helping the tissue to regenerate. Traditional ceramic implants are hydroxyapatite, but given their low mechanical properties, they have been replaced with better inert ceramics. Therefore, this study aims at manufacturing titanium dioxide scaffolds through various techniques, using collagen, polyvinyl alcohol (PVA), sodium chloride, and corn flour as binders to influence pore size. Scaffolds were characterized by a Scanning Electron Microscope (SEM) and evaluated by compression and degradability tests in a Simulated Body Fluid (SBF). The prepared scaffolds had mechanical behaviors with ranges within the bone parameters; among them, the scaffold obtained by infiltration with 10% PVA presented values of compression strength (6.75 MPa), elastic modulus (0.23 GPa), and porosities (54-67%) closer to the values of the trabecular bone.